2000 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings (Cat. No.00CH37100)
DOI: 10.1109/icassp.2000.860220
|View full text |Cite
|
Sign up to set email alerts
|

On model quality and evaluation in speaker verification

Abstract: This paper addresses differences between operational speaker verification (SV) systems and laboratory experiments in terms of performance and methods for measuring performance. It is concluded that operational SV systems need an indication of the quality of newly enrolled speaker models, to decide whether t o re-enrol or request more enrolment material. We have investigated the impact of ASR errors on model quality. While attempting to design measures for the quality of speaker models we have developed a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Another different approach [2] to check model quality introduces the distance Z between LLR scores from clients and from impostors for a given model:…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Another different approach [2] to check model quality introduces the distance Z between LLR scores from clients and from impostors for a given model:…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The 'leave-one-out' method [1] has the problem of an excessive computational cost. The Z method [2] uses impostor data. The method introduced by the authors in [3] overcomes these two problems but, as it happens with the first two methods, it needs the speaker model to evaluate quality.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion function is adapted to rely more on the biometric traits that are less prone to error in noisy conditions. Other studies concerned with quality estimations in the field of speaker recognition include: [7] in which model quality assessment methods are studied to adapt the model training process and [1] in which quality-based feature selection is proposed to improve the performance of speaker recognition systems.…”
Section: Introductionmentioning
confidence: 99%
“…The overall analysis of access calls showed that the false reject rate for individual clients were very high for a substantial pro portion of the callers [4], [5]. It turned out that these errors were related to the quality of the speaker models after enrolment [6]. This model quality is strongly dependent on consistent behav iour of the user during enrolment.…”
Section: Introductionmentioning
confidence: 99%